INFLUENCE OF HARMFUL SUBSTANCE IN THE AIR ON IMMUNITY SYSTEM OF CHILDREN IN DIFFERENT SEASONS - Савчук, Л. Я.; Семчук, Я. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the conditions of permanent growth of transport motor vehicles and a plenty of industrial enterprises maintenance of harmful matters, which affect children’s organism and cause the origin of diseases of theirs immunity system. Just as primary there is determination of cold allergies is whey cryoglobulines to the scrining autoimmunity and allergies. Annual statistical research was conducted 100th children during 2013-2017 years. It gave possibility to define the row of conformities to the law in the origin of cryoglobulinemies. In the conditions of permanent growth of transport motor vehicles and a plenty of industrial enterprises maintenance of harmful matters, which affect children’s organism and cause the origin of diseases of theirs immunity system. Just as primary there is determination of cold allergies is whey cryoglobulines to the scrining autoimmunity and allergies. Annual statistical research was conducted 100th children during 2013-2017 years. It gave possibility to define the row of conformities to the law in the origin of cryoglobulinemies.